Peningkatan Motorik Kasar Pada Anak Usia Dini Berbasis Belajar Sambil Bermaian Melalui Permainan Tradisional Engklek di PAUD Kober Al-Maarif - Sinta Nurul Paujiah; Nur Safariani; Aqvina Indriani; Nila Nurmala; Aisah Prihatini; Sandriani Sandriani; Sri Utami Asmarani (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: Early age is a golden opportunity for children to learn, so it is called the golden age. Early childhood education is a form of education that focuses on laying the foundation for physical growth and development (fine and gross motor coordination). the learning techniques used must make children happy, so the method used is learning-based education while playing and the Engklek game is one of the traditional games that can be used. Purpose: The purpose of this activity is to implement play-based learning through the medium of traditional crank games to improve gross motor development in early childhood at PAUD Kober Al-Maarif. Method: The method used in health promotion is education based on learning while playing. This health promotion was carried out at PAUD Kober Al-Maarif Lakbok with a total of 35 participants with a series of activities through 4 stages, namely 1) selection of targets and places, 2) preparation of facilities and infrastructure, 3) implementation of activities, 4) evaluation. Results: based on the results of the evaluation carried out by the learning while playing method, it gave a positive response to the participants. the participants enjoyed the series of events from start to finish with joy. Through this activity, children are more able to explore their imagination and bring out their creativity and talents. Conclusion: This activity can be carried out as a game to train gross motor skills in early childhood by using the traditional crank game as media. In addition, not only gross motor skills but also exploring other learning that can be included in playing activities by recognizing numbers and letters and counting.